Upwelling of hydrothermal solutions through ridge flank sediments shown by pore water profiles. - Maris, C. R. P., Bender, M. L. (1982)
BIB Now: 4819
English
Keywords: HV, GL, OC -- Upwelling of hydrothermal solutions through ridge flank sediments shown by pore water profiles